Malacofauna continental holocena (región Pampeana, Argentina) - Steffan, Pamela Guillermina (2014)
In this study the molluscan fauna recovered from six archaeological sites of the Interserrana Bonaerense area is analyzed. Three geographical sectors were studied in this area: I) Middle river basin of Quequén Grande river; II) Southwest of the Interserrana area, and III) Upper river basin of the Tapalqué stream. The systematic review of the continental mollusks recovered was complemented with quantitative, stratigraphical and chronological data for each site since the early Holocene until the present. Additionally, ecological requirements and modern distribution patterns of the taxa recorded were considered in order to search for eventual palaeoenvironmental variations in space and time. A total of 15 taxa (14 Gastropoda and one Bivalvia) were identifi ed in the Luján Formation deposits from southeastern Buenos Aires Province. The fi rst Holocene records for “Aplexa” minor (d’Orbigny), Drepanotrema kermatoides (d’Orbigny), Antillorbis nordestensis (Lucena), Omalonyx unguis d’Orbigny and Pisidium sp. are reported in the Bonaerese Interserrana area. Overall, the mollusks suggest palustrine habitats at the beginning of the early Holocene. During the middle Holocene, they suggest higher humidity (increase of the precipitation pattern) ca. 4.9 kyrs BP and ca. 4.7 kyrs BP. At the beginning of the late Holocene they indicate a general arid trend interrupted by brief humid episodes registered ca. 2.5 kyrs BP and ca. 2.2 kyrs BP. The integration and correlation of molluscan records in spatial and temporal scales allowed recognizing geographical displacements (i.e. Retidiscus reticulatus Fonseca & Thomé) which represent biotic responses to Holocene climate variations as well as local environmental differences for stratigraphical sequences of similar chronologies.